Connections and the allocation of public benefits - Carol Newman; Mengyang Zhang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
We explore the relationship between connections and public transfers in decentralized poverty-targeting programmes. Using panel data from Vietnam we find evidence that households with connections to local government are more likely to be classified as poor, the main determinant of whether households receive public benefits/supports. Social connections play a role by allowing politically connected households to receive supports without being reprimanded by their local community. We identify provision of information as a mechanism through which households use their connections to obtain the poverty classification, suggesting that information campaigns may be an effective means of eliminating local level corruption in poverty-targeting programmes.
Keywords: O12; I3; D1; 330; political connections; social connections; decentralization; poverty targeting; Vietnam